Korelasi Kepemimpinan Dan Kedisiplinan Terhadap Kinerja Guru Dengan Motivasi Sebagai Variabel Intervening - Rosmawati; Indrayani, Emmy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: The research aimed to explore the influence of leadership and discipline on teacher performance, with motivation serving as an intervening variable. Methode: Employing a descriptive quantitative approach, path analysis using Smart Partial Least Square (PLS) software version 3.0 was utilized Finding: The findings indicate that motivation and effective leadership also positively impact teacher performance. However, the direct influence of discipline on teacher motivation and performance appears less significant, highlighting the intricate nature of motivational factors in educational settings. Theoretical contribution/Originality: The study offers insights into the nuanced dynamics of these factors and their implications for educational practices, thereby enriching theoretical frameworks in the field. Practitioner/Policy implication: These findings have practical implications for school administrators and policymakers regarding the importance of fostering a supportive and motivating work environment for teachers through effective leadership practices. Additionally, it emphasizes the need for holistic management strategies and addressing factors beyond disciplinary action to improve overall teacher performance. Research limitation: Discrepancies in respondent understanding during questionnaire completion may have influenced the accuracy of the data collected.